Potassium Improvement of Quality in Fruits and Vegetables Through Hydroponic Nutrient Management - Asaduzzaman, Md; Asao, Toshiki (IntechOpen, 2018)
The book Potassium - Improvement of Quality in Fruits and Vegetables Through Hydroponic Nutrient Management provides useful information regarding potassium nutrition management in hydroponic cultivation, which will help in producing quality horticultural crops. The first few chapters describe the role of potassium nutrition in plants, its interaction with other nutrients, its source fertilizers, the role in postharvest produce qualities, and human nutrition. Potassium fertilizer management, its metabolism in plants, and cultivation techniques of fruits and leafy vegetables are also included in the middle section. The final chapter illustrates the software development for the calculation of hydroponic nutrients including potassium for easy management of cultural solution. As a whole, this book covers several major aspects on the topic for making it a complete and useful resource.